A Novel Machine Learning-derived Radiomic Signature of the Whole Lung Differentiates Stable From Progressive COVID-19 Infection: A Retrospective Cohort Study. Issue 6 (November 2020) - Fu, Liping; Li, Yongchou; Cheng, Aiping; Pang, PeiPei; Shu, Zhenyu
Abstract : Objective: This study aimed to use the radiomics signatures of a machine learning-based tool to evaluate the prognosis of patients with coronavirus disease 2019 (COVID-19) infection. Methods: The clinical and imaging data of 64 patients with confirmed diagnoses of COVID-19 were retrospectively selected and divided into a stable group and a progressive group according to the data obtained from the ongoing treatment process. Imaging features from whole-lung images from baseline computed tomography (CT) scans were extracted and dimensionality reduction was performed. Support vector machines were used to construct radiomics signatures and to compare differences between the 2 groups. We also compared the differences of signature scores in the clinical, laboratory, and CT image feature subgroups and finally analyzed the correlation between the radiomics features of the constructed signature and the other features including clinical, laboratory, and CT imaging features. Results: The signature has a good classification effect for the stable group and the progressive group, with area under curve, sensitivity, and specificity of 0.833, 80.95%, and 74.42%, respectively. Signature score differences in laboratory and CT imaging features between subgroups were not statistically significant ( P >0.05); cough was negatively correlated with GLCM Entropy_angle 90_offset4 ( r =−0.578), but was positively correlated with ShortRunEmphhasis_AllDirect_offset4_SD ( r =0.454); C-reactive protein was positively correlated with Cluster Prominence_ AllDirect_offset 4_ SD ( r =0.47). Conclusion: The radiomics signature of the whole lung based on machine learning may reveal the changes of lung microstructure in the early stage and help to indicate the progression of the disease. Abstract : Supplemental Digital Content is available in the text.